Evaluating the effect of technology transformation on the electricity utility industry. (December 2017) - Castaneda, Monica; Franco, Carlos J.; Dyner, Isaac
Abstract: The technology shift from fossil-fuelled systems to renewable energies has been promoted by governments with the purpose of decarbonising the power industry. However, rapid technology progress has prompted disruptive changes that transformed market structures. Incumbent electricity utilities, particularly those based on fossil-fuel plant, are shifting from their stable and predictable situation to confront challenges from those that offer alternative energy services. In this new environment, the industry will benefit from mid- to long-term sector foresight. The paper studies the potential impact of renewable energy sources (RES) on electricity systems, specifically on the generation and distribution businesses. For this purpose, a fairly detailed and integrated supply and demand-based system dynamics model has been built to quantify the extent of their potential impact; the model disaggregates the household sector, which may generate a significant part of its electricity using rooftop solar energy. This is illustrated by examining a utility engaged in the generation and distribution businesses in the Colombian electricity market. Through simulation runs, this paper concludes that, subject to policy and all other things remaining equal, solar rooftop generation is a major threat for utilities; while the generation business is most affected in the short-term, the distribution business is the one most impacted in the long-term, and jointly they may induce the utility "death spiral".